2016
DOI: 10.3174/ajnr.a4821
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Wisely

Abstract: SUMMARY: Diagnostic imaging is the most rapidly growing physician service in the Medicare and privately insured population. The growing share of medical costs devoted to imaging procedures has led to increasing concerns among the key federal agencies and private payers. In an attempt to educate health care providers, patients, and families on the importance of making optimal clinical decisions, the American Board of Internal Medicine Foundation organized the Choosing Wisely initiative with strong collaboration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…es and the lack of radiation exposure. 35,36 Our study showed a disparity in capturing intracranial abnormalities between MRI and CT: 29.6% vs. 4.9% for overall neuroimaging abnormalities, and 4.9% vs. 1.1% for serious intracranial abnormalities. These findings suggest that using MRI rather than CT will increase the probability of capturing both overall and serious neuroimaging abnormalities in patients with primary headache disorder, which is consistent with the neuroimaging recommendation made in the Choosing Wisely campaign.…”
Section: Jcnmentioning
confidence: 72%
“…es and the lack of radiation exposure. 35,36 Our study showed a disparity in capturing intracranial abnormalities between MRI and CT: 29.6% vs. 4.9% for overall neuroimaging abnormalities, and 4.9% vs. 1.1% for serious intracranial abnormalities. These findings suggest that using MRI rather than CT will increase the probability of capturing both overall and serious neuroimaging abnormalities in patients with primary headache disorder, which is consistent with the neuroimaging recommendation made in the Choosing Wisely campaign.…”
Section: Jcnmentioning
confidence: 72%
“…Use of edge density imaging in our study yielded 40% improvement in diagnostic AUC over the FA scalar. Added value of edge density imaging over neurocognitive testing is also important given concerns regarding the cost of neuroimaging [52] and the current barriers to adoption of DTI for mild TBI in routine clinical practice and in medicolegal settings [53]. Lack of correlation between edge density imaging and neurocognitive testing potentially suggests an underlying level of damage to the brain from mild TBI that might precede identifiable neuropsychological deficits, although the small sample size of our study limits its statistical power for determining such correlations.…”
Section: Discussionmentioning
confidence: 96%
“…14 In the follow-up review authored by Buethe et al, the authors described critical elements of appropriate-use criteria as defined by the Centers for Medicare and Medicaid services. These imaging criteria must “be developed or endorsed by national professional medical specialty societies or provider-led entities, be scientifically valid and evidence-based, and must be based on published studies that are reviewable by stakeholders.” 15 These concerted efforts are vital in shifting the onus of responsible utilization of advanced imaging toward providers and away from proprietary guidelines companies.…”
Section: Discussionmentioning
confidence: 99%